PEMANFAATAN SARANG SEMUT (Myrmecodia pendens) ASAL KALIMANTAN SELATAN SEBAGAI ANTIBAKTERI - Farida Crisnaningtyas; Andri Taruna Rachmadi (Kementerian Perindustrian, 2010)
The use of ant nests (Myrmecodia pendens) native of Borneo as an antibacterial. The aim of this research is to make the crude drug from the ant nest, simply extracting, condensing and test the ability of anti-bacterial properties of ant nests. This study covers the development of these extracts, proximate analysis, and test the antibacterial activity of plant-ant nest. Parameters measured were the growth of antibacterial activity against Salmonella sp., E. coli and Bacillus sp. showed by inhibition (clear zone). The results showed that plant-ant nests have antibacterial power. Ethanol extract of the ant nests provide a better inhibition compared with water extraction ant nests. Antibacterial activity of the ant nest extracts can be applied both in gram- positive and gram-negative bacteria. Key wood : ant nest, antibacterial, inhibition capability